Developing 3D FEM tool for modeling structure-soil-structure interaction (3SI) observed in the NUPEC field experiment - Ereño, Mary Nathalie C.; Quinay, Pher Errol B. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
The presence of structures in an area affects the seismic wave propagation during a seismic event. Structure-soil-structure interaction (3SI) is observed when the interaction of the structures and the ground within the area is evident through their dynamic response. Many single-structure earthquake simulations have already been conducted in the Philippines, but without consideration of 3SI effect. This study aims to develop a three dimensional finite element method (3D FEM) tool for modeling 3SI. The tool is capable of generating a model with multiple structures for physics based dynamic response analysis. To address the computationally expensive nature of this approach, a modified model generation tool based on Octree partitioning and Progressive Solid Models, is proposed. To check the validity of the developed 3D FEM tool, the forced harmonic vibration experiment from Nuclear Power Engineering Corporation (NUPEC) test was simulated. The developed tool was able to draw similar observations in dynamic response trend for 3SI that was observed experimentally. Another simulation with complex built environment was conducted. Results revealed response amplification and reduction for cases of with and without adjacent structure
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Soil-structure interaction; Finite element method